Estimating medieval market integration: Evidence from exchange rates - Oliver Volckart; Nikolaus Wolf (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2004)
In this paper we present a new method for estimating market integration under a commodity money system such as that which existed in Europe until the demise of the gold standard. The approach is based on the analysis of deviations between exchange rates and parity, which under conditions of a perfectly functioning and fully integrated market should not exceed the bullion points. Consequently the time needed for adjustment, following a violation of the bullion points, can be used as an indicator of market imperfections and as a measure of integration. We apply this approach to trade between late medieval Flanders, Lübeck and Prussia, our results showing that Flanders-Lübeck constituted a much better-integrated market than Flanders-Prussia. Moreover, the results indicate that the degree of market integration increased between the early fourteenth and the middle of the fifteenth century.
Keywords: F15; F31; N13; N23; 330